ANALISA USAHA PENGGEMUKAN DOMBA DENGAN PAKAN FERMENTASI MILIK BAPAK ZAINAL ARIFIN DI DESA BANDAR KECAMATAN KEDUNGMULYO KABUPATEN JOMBANG - Muhammad Zein Solikin (Jurnal Sains Peternakan, 2013)
This research executed in husbandry belongs to the Mr. Zainal Arifin in countryside of bandar of subdistrict Kedungmulyo Jombang regency. From date 17 October up to 17 November 2013. Intention of this research is to Analyse the effort fattening sheep with feed fermentated. Method used in this research method of survey that is a data collecting conducted interview to breeder of sheep directly. Base of data obtained tabulation later. Parameter perceived in this research is fixed cost,Erratic Expense, Acceptance, Advantage, Break Event Point and  Elegibility of effort.Result of research show productions cost of equal to Rp. 187.547.625 Acceptance equal to Rp. 231.981.400, advantage equal to Rp. 44.433.775That height of productions cost influenced  by level of expense of buy of feed that is equal to 62,25 %, followed with expense of buy of seed and labour equal to 28,58 % and 0,59 %, this calculations then get Break Event Point of price of Rp, 56,894 Break Event Point production 26,89 / Kg and R/C ratio 1,24 .Through result of this research is iferential that fattening sheep feed fermentated feasible for be continued.Key words : Analyse, Fattening sheep, Feed Fermentated.